2019
DOI: 10.32938/sc.v4i01.460
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Model Pengelolaan Lahan Kering Dataran Tinggi Berbasis Agroforestri Tradisional di Pulau Timor

Abstract: Tujuan diadakannya penelitian ini untuk; (i) mengidentifikasi model pengelolaan lahan kering dataran tinggi berbasis agroforestri tradisional; (ii) mengukur seberapa besar kontribusi pendapatan rumah tangga masyarakat yang diperoleh pada masing-masing model pengelolaan lahan kering dataran tinggi berbasis agroforestri tradisional. Penelitian ini dilaksanakan di Pulau Timor khususn ya di kecamatan Miomaffo Barat, Kabupaten Timor Tengah Utara, Nusa Tenggara Timur pada bulan Oktober-Desember 2016 menggunakan meto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
7
0
2
Order By: Relevance
“…Agroforestry (AF) is a land-use management system that combines agriculture and forest practices by planting agricultural crops along with forestry trees to be managed as a sustainable system (Sarminah et al 2018;Agu et al 2019). From an agroecological perspective, agroforestry forms multi-strata canopy layers that are beneficial for soil conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Agroforestry (AF) is a land-use management system that combines agriculture and forest practices by planting agricultural crops along with forestry trees to be managed as a sustainable system (Sarminah et al 2018;Agu et al 2019). From an agroecological perspective, agroforestry forms multi-strata canopy layers that are beneficial for soil conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Hutan di Indonesia semakin memprihatinkan sebagai dampak dari berbagai persoalan mendasar yang melilit sektor kehutanan sangat kompleks, akumulasi berbagai dimensi faktor penyebab meningkatnya laju kerusakan hutan dan lahan (Agus, 2017). Tuntutan ekonomi, lapangan pekerjaan yang sulit dan kebutuhan hidup menuntut petani membuka lahan.…”
Section: Pendahuluanunclassified
“…The earlier studies in Mountain Mutis Area discussed the traditional agroforestry system, land-use change, and livelihood aspects of the native inhabitants. For example, Agu & Neonbeni (2019) classified the traditional high-land agroforestry model in the West Miomaffa area adjacent to the east side of the Mountain Mutis Nature Reserve into three models: kono agrosilviculture model, suf silvopastur model, and poan agrosilvopastur model. Pujiono, et al (2019) showed the land-use changes and deforestation in the Mutis area over three decades using GIS analysis.…”
Section: Traditional Land Systemmentioning
confidence: 99%